2004
DOI: 10.1093/ndt/gfh1014
|View full text |Cite
|
Sign up to set email alerts
|

Early post-transplant renal allograft function between 1990 and 1998 in Spain

Abstract: Despite poorer renal function at 3 months in 1998 than in 1990, renal allograft survival has improved in Spain between 1990 and 1998. This result is partly explained by a slower deterioration of renal function during the first year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In renal transplants, the implantation of a single kidney combined to different injuries after transplantation leads to chronic graft dysfunction. Epidemiological studies have shown that about 60% of renal transplants have a glomerular filtration rate <60 ml/min/1.73 m 2 and about 15% <30 ml/min/ 1.73 m 2 at 1 year [14,15].…”
Section: Graft Dysfunction As a Cardiovascular Risk Factormentioning
confidence: 99%
“…In renal transplants, the implantation of a single kidney combined to different injuries after transplantation leads to chronic graft dysfunction. Epidemiological studies have shown that about 60% of renal transplants have a glomerular filtration rate <60 ml/min/1.73 m 2 and about 15% <30 ml/min/ 1.73 m 2 at 1 year [14,15].…”
Section: Graft Dysfunction As a Cardiovascular Risk Factormentioning
confidence: 99%